Blue labyrinth - Preston, Douglas J.; Child, Lincoln (New York : Vision, 2015)
A long-buried family secret resurfaces when one of Aloysius Pendergast's most implacable enemies shows up on his doorstep as a murdered corpse.
Keywords: Pendergast, Aloysius (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Family secrets -- Fiction